Open problems. (New Scientist, 2026)
The article focuses on the dual-edged nature of open-source software, highlighting its widespread use and benefits alongside emerging risks. It notes that open-source code, while enabling collaborative improvements and accessibility, has been adapted for military purposes, such as guiding inexpensive Ukrainian cruise missiles. The piece also contrasts AI development approaches, with U.S. companies relying on proprietary models with built-in safeguards, while Chinese open-source AI models are freely available but less regulated, complicating efforts to control harmful outputs. Overall, the article emphasizes that open-source software facilitates innovation and problem-solving but also introduces challenges in security and regulation.